Robot Grasping Based on Stacked Object Classification Network and Grasping Order Planning - Liu, Chenlu (2022)
This work was supported by the National Key R&D Program of China (No.2018YFB-1308400) Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.